Peculiarities of demand for medicines and assessment of the consequences of introducing co-payment in Kazakhstan - Spankulova, L.S.; Mukhamediyev, B.M.; Bukatov, Y.B. (BUKETOV BUSINESS REVIEW, 2024)
Object: In the context of the population's growing need for medical care and limited resources of the healthcare system, the issue of assessing the population's demand for medical services, especially for medicines, in both developed and developing countries becomes relevant. The study aims to determine the characteristics of the population's demand for medicines in the Republic of Kazakhstan and assess the impact of co-payment mechanisms on medicine consumption. Methods: To achieve this goal, we conducted a sociological survey of the population in all regions of Kazakhstan, with the participation of 1638 respondents. Questionnaire data were estimated using a logarithmic model. Findings: As a result of evaluating the logarithmic model, we identified the main factors influencing the demand for medicines. An individual's poor health state increases the demand for and consumption of medicines. We observed decreased demand for medicines among those individuals who assessed their health status by non-medical factors. Individuals who used the services of private medical institutions increased their demand for medicines, unlike those individuals who used the services of specialized medical institutions. A large amount of time spent traveling to medical centers is also one of the factors in increasing drug consumption. Such factors as visits to emergency medical care, the presence of chronic diseases in family members, the gender and place of residence of the individual, and a large number of children in the family influence high demand. Conclusions: The logarithmic model results show many factors influencing the demand for medicines; the introduction of co-payment further expands the variability of factors influencing the volume of medicine consumption by the population. Various co-payment mechanisms can both reduce consumption and encourage drug consumption.